Incidence of thromboembolic events following administration of four-factor prothrombin complex concentrate (4F-PCC) for oral anticoagulation reversal. Issue 194 (October 2020) - Makhoul, Therese; Kelly, Gregory; Kersten, Brian; Nadler, Megan; Zammit, Christopher G.; Jones, Courtney M.C.; Scott, Rachael; Acquisto, Nicole M.
Abstract: Introduction: Prothrombin complex concentrates (4F-PCC) for anticoagulation reversal pose a risk of thromboembolism although data are limited. This study aims to quantify thromboembolic events (TE) and describe associations. Materials and methods: Retrospective, two-center, study of patients receiving 4F-PCC between September 2013 and December 2017 for warfarin or direct oral anticoagulant (DOAC) reversal. Primary outcome was in-hospital TE incidence and secondary outcomes were to describe characteristics associated with TE. Data are reported descriptively and analyzed with bivariate and multivariate analyses. Results: 542 patients were included (mean age 73 ± 14 years, 58% male, 76.6% warfarin/23.4% DOAC reversal). Most had intracranial hemorrhage (68.5%) or were undergoing an emergent procedure (13.4%). Fifty patients (9.2%) experienced in-hospital TE and most (62%) occurred within 7 days of 4F-PCC. Younger age (66 vs. 74 years, p < 0.01), presence of a hypercoagulable risk factor (46% vs. 26%, p < 0.01), indication for anticoagulation (p = 0.008), higher 4F-PCC dose (2148 vs. 2000 units, p < 0.01), and longer hospital length of stay (LOS) (21.5 vs. 7 days, p < 0.01) were associated with TE following bivariate analysis. Multivariate analysis identified anticoagulation indication of venous thromboembolism or "other" (e.g., antiphospholipid syndrome, Factor V Leiden) were independently associated with higher incidence of TE compared to receiving anticoagulation for atrial arrhythmia (p = 0.05). Hospital LOS ≥ 7 days was associated with threefold greater odds of TE compared to <7 days (p = 0.003). Conclusions: In-hospital TE following 4F-PCC was 9.2%, most events occurred within 7 days, and younger age, indication for anticoagulation, and LOS were independently associated with TE which may influence treatment selection. Highlights: Thromboembolic complications occur with 4F-PCC for oral anticoagulation reversal. This is the largest cohort and highest rate reported; 50/542 (9.2%) of patients. Most events occurred within 7 days (62%) and 42% occurred within 72 h. Age, anticoagulation indication, and length of stay were associated with events.